2015
DOI: 10.1093/mnras/stv1007
|View full text |Cite
|
Sign up to set email alerts
|

Quenching and morphological transformation in semi-analytic models and CANDELS

Abstract: We examine the spheroid growth and star formation quenching experienced by galaxies since z ∼ 3 by studying the evolution with redshift of the quiescent and spheroid-dominated fractions of galaxies from the CANDELS and GAMA surveys. We compare the observed fractions with predictions from a semi-analytic model which includes prescriptions for bulge growth and AGN feedback due to mergers and disk instabilities. We facilitate direct morphological comparison by converting our model bulgeto-total stellar mass ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 167 publications
(203 reference statements)
7
77
0
Order By: Relevance
“…Further, Brennan et al (2015) confirmed that a model adding the disk instabilities for bulge growth agrees better with the observed galaxy distribution on the sSFR-Sérsic index plane than a model in which bulges grow only through mergers. By implementing the bulge growth model with the mergers and disk instabilities into the semi-analytic galaxy formation code, Tonini et al (2016) produced two distinct populations of bulges: merger-driven bulges, similar to classical bulges and instability-driven bulges, similar to pseudo-bulges.…”
Section: The Formation Of Targeted Galaxiessupporting
confidence: 60%
See 1 more Smart Citation
“…Further, Brennan et al (2015) confirmed that a model adding the disk instabilities for bulge growth agrees better with the observed galaxy distribution on the sSFR-Sérsic index plane than a model in which bulges grow only through mergers. By implementing the bulge growth model with the mergers and disk instabilities into the semi-analytic galaxy formation code, Tonini et al (2016) produced two distinct populations of bulges: merger-driven bulges, similar to classical bulges and instability-driven bulges, similar to pseudo-bulges.…”
Section: The Formation Of Targeted Galaxiessupporting
confidence: 60%
“…The formation mechanisms of them are not clear. The disk instabilities in secular evolution and minor mergers may be another additional channels for bulge growth and morphological transformation (Porter et al 2014;Brennan et al 2015). In the near future, the on-going large IFS surveys will provide larger sample of galaxies with outside-in assembly mode, and help people to understand the origins of outside-in assembly mode.…”
Section: Implications In the View Of Quenchingmentioning
confidence: 99%
“…On the other hand, galaxies with n>2 (implying more dominant bulges and higher central densities) have significantly lower sSFRs than the main ridgeline of the star formation sequence. Brennan et al (2015) presented a schematic diagram of how the various physical mechanisms could move galaxies around the sSFR-n plane, accounting for dry and wet mergers, disk instabilities, galaxy harassment, AGN feedback, and other slow gas-depletion processes. However, the relevant result from the present data is that both galaxy size and n alone are insufficient to isolate quiescent galaxies with low sSFRs.…”
Section: Which Role Do Galaxy Size and Sérsic Index Play Inmentioning
confidence: 99%
“…Choi et al 2014;Brennan et al 2015). Given the number of free parameters, studying the evolution of the distribution of galaxies in star-formation-rate/stellar-mass/morphology planes can only help to constrain the role of different processes in shutting down star formation in combination with detailed models which help to link cause and effect.…”
Section: Introductionmentioning
confidence: 99%